Tratamento para rizogênese incompleta em dentes com necrose pulpar: revisão de literatura - Leite, Andrei Mossi (2019)
Incomplete rhizogenesis is usually related to some traumatic event or infection of the root canal, in which the apical closure of the root does not take place. There are some forms of treatment such as apexification and induction of apicigenesis, together with materials such as mineral trioxide aggregate (MTA), calcium hydroxide and the revascularization technique, which contribute to the induction of apical closure in cases of pulpal necrosis. The objective of this work is to verify, through a literature review, which form of treatment for incomplete rhizogenesis results in higher rates of clinical success. Clinical research articles were collected from the Pubmed/Medline database, from the period 2000 to 2019. Articles were selected that investigated the treatment of immature teeth with pulp necrosis using calcium hydroxide, MTA and revascularization. According to studies, MTA and calcium hydroxide have high success rates and induce apical closure. However, MTA induces apical closure in a shorter time and has a lower incidence of root fracture. Revascularization has the advantage of restoring root thickness and length, but its success rate is lower. It is concluded that all treatments are capable of inducing apical closure, but treatment with MTA stands out for its predictability, efficiency and safety.